2021
DOI: 10.3390/app11062621
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Contrast of Pseudothermal Ghost Images Based on the Measured Signal Distribution of Speckle Fields

Abstract: In this study, we examine the quality of microscale ghost images as a function of the measured histographic signal distribution of the speckle fields from a nonuniform pseudothermal light source. This research shows that the distribution of the detected signal level on each pixel of the camera plays a significant role in improving the contrast-to-noise ratio (CNR) of pseudothermal ghost imaging. To our knowledge, the scaling of CNR with different pixel intensity distributions of the speckle fields is observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
3
3
0
Order By: Relevance
“…While the TGI demonstrated good CNR, the corresponding resolution was lower (R = 1.10). Overall, our experimental results were consistent with existing theories [18,19], enabling subsequent comparisons with the SGI method.…”
Section: Experiments and Simulation Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…While the TGI demonstrated good CNR, the corresponding resolution was lower (R = 1.10). Overall, our experimental results were consistent with existing theories [18,19], enabling subsequent comparisons with the SGI method.…”
Section: Experiments and Simulation Resultssupporting
confidence: 86%
“…Based on the findings from previous pseudo-thermal ghost imaging experiments [19], we have confirmed a significant degradation in the quality of ghost images as the speckle size increases. However, it is observed that with larger speckle sizes, the speed of image appearance during reconstruction also increases.…”
supporting
confidence: 73%
See 2 more Smart Citations
“…Compared to ghost imaging based on entangled photon pairs, PGI is very flexible regarding wavelength, e.g., X-ray ghost imaging has been demonstrated [9][10][11][12]. Thus, in recent years, PGI has been investigated extensively [13][14][15][16][17] to overcome the limitations of image quality.…”
Section: Introductionmentioning
confidence: 99%